Adhesive composition, adhesive for masking film made using same, and adhesive film for masking

The adhesive composition with specific acrylate monomers and a crosslinking agent enables light peeling without substrate damage, addressing the limitations of existing compositions by ensuring effective adhesion and contamination resistance.

JP7622428B2Active Publication Date: 2025-01-28MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020216654
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-01-28
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

Existing adhesive compositions for masking films fail to provide adequate adhesion strength for high-speed peeling without damaging the substrate, leading to potential contamination and reduced workability.

Method used

An adhesive composition comprising specific ratios of acrylate monomers with alkyl groups of 4 to 12 and 1 to 3 carbon numbers, 2-hydroxyethyl monomer, and a crosslinking agent, which allows for light peeling regardless of speed, maintaining adhesion and preventing contamination.

Benefits of technology

The adhesive composition ensures effective peeling without substrate damage or contamination, suitable for various applications including masking films, display labels, and touch panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622428000001
    Figure 0007622428000001
  • Figure 0007622428000002
    Figure 0007622428000002
  • Figure 0007622428000003
    Figure 0007622428000003
Patent Text Reader

Abstract

To provide an adhesive composition which can be peeled with light force regardless of peeling speed when used as an adhesive, is less likely to cause contamination when peeled from an adherend, and can be used for an adhesive film for masking.SOLUTION: An adhesive composition contains an acrylic resin (A), in which the acrylic resin (A) is an acrylic resin obtained by copolymerization of a copolymerization component (a) containing an acrylate monomer (a1) having an alkyl group having 4 to 12 carbon atoms, an acrylate monomer (a2) having an alkyl group having 1 to 3 carbon atoms, and a 2-hydroxyethyl methacrylate monomer (a3), a content ratio of the acrylate monomer (a2) having the alkyl group having 1 to 3 carbon atoms in the copolymerization component (a) is 20 wt.% or more, and a content ratio of the 2-hydroxyethyl methacrylate monomer (a3) is 6 wt.% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition, an adhesive for masking films using the same, and an adhesive film for masking. In particular, the present invention relates to a pressure-sensitive adhesive composition which, when used as an adhesive, has excellent releasability and resistance to contamination of adherends regardless of the peeling speed, and can be used for adhesive films for masking, etc., an adhesive for masking films using the pressure-sensitive adhesive composition, and an adhesive film for masking having an adhesive layer made of the adhesive on a film. [Background technology]

[0002] Conventionally, re-peelable adhesive films have been used to temporarily fix and protect various components when processing them. In recent years, for example, they have been used as masking adhesive films for temporary surface protection of circuit boards such as flexible printed circuit (FPC) boards and ITO transparent electrode layers, and as surface protection adhesive films for flat panel displays and touch panels, and are often peeled off at a relatively high speed from the viewpoint of work efficiency. For this reason, if the adhesive strength is high during high-speed peeling, the work efficiency is poor, and in the manufacturing process of FPC boards and ITO transparent electrode layers, the laminated board of the FPC board or ITO transparent electrode layer may be damaged when the adhesive film is peeled off, or contamination may occur due to adhesive residue. Therefore, it is required that the adhesive film can be peeled off at high speed with light force without leaving any adhesive residue. In addition, if the peeling force is too light, there is a risk of peeling off during the manufacturing process, so moderate adhesive strength is required.

[0003] As an example of an adhesive composition used in such a surface-protecting adhesive film, Patent Document 1 discloses a removable adhesive composition having low adhesive strength during high-speed peeling and high adhesive strength during low-speed peeling to such an extent that problems such as lifting or peeling do not occur, and having particularly high transparency, as well as a removable adhesive layer and removable adhesive sheet, the removable adhesive composition comprising 100 parts by mass of a polymer having a glass transition temperature of less than 0°C and 0.05 to 3 parts by mass of a (meth)acrylic polymer containing, as a monomer unit, a (meth)acrylic monomer having a weight-average molecular weight of 1,000 or more and less than 30,000.

[0004] However, the technology of Patent Document 1 contains a (meth)acrylic polymer having a weight-average molecular weight of 1,000 or more and less than 30,000 as an essential component, which may cause contamination of the adherend after peeling.

[0005] Patent Document 2 discloses a pressure-sensitive adhesive composition in which the peel force has little speed dependency and workability does not decrease during high-speed peeling, and a surface protection film to which the pressure-sensitive adhesive composition is applied, the pressure-sensitive adhesive composition comprising an acrylic copolymer containing hydroxyl groups and carboxyl groups as reactive functional groups and having a glass transition temperature (Tg) of -40°C or lower and -80°C or higher; and an aromatic polyfunctional isocyanate compound as essential components.

[0006] However, the technology of Patent Document 2 uses an acrylic copolymer having a glass transition temperature (Tg) of -40°C or lower and -80°C or higher. Generally, a low glass transition temperature reduces workability during high-speed peeling, and therefore there is a possibility that sufficient peelability cannot be obtained during high-speed peeling. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-079360 A [Patent Document 2] JP 2005-097451 A Summary of the Invention [Problem to be solved by the invention]

[0008] Under these circumstances, an object of the present invention is to provide a pressure-sensitive adhesive composition that can be peeled off with a light force regardless of the peeling speed, that is unlikely to cause contamination when peeled off from an adherend, and that can be used for pressure-sensitive adhesive films, etc.

[0009] Another object of the present invention is to provide an adhesive for masking films using this adhesive composition, and an adhesive film for masking having an adhesive layer made of this adhesive on a film. [Means for solving the problem]

[0010] As a result of intensive research by the inventors to solve the above problems, they discovered that in a pressure-sensitive adhesive composition using an acrylic resin, when the copolymerization components constituting the acrylic resin contain an acrylate monomer having two types of alkyl groups, one with a low carbon number and one with a high carbon number, and a 2-hydroxyethyl methacrylate monomer, and when the acrylate monomer having an alkyl group with a low carbon number and the 2-hydroxyethyl methacrylate monomer are contained in specific amounts, the pressure-sensitive adhesive composition can be peeled off with light force regardless of the peel speed, is unlikely to cause contamination when peeled off from an adherend, and can be used for pressure-sensitive adhesive films, etc., and thus completed the present invention.

[0011] That is, the present invention provides the following [1] to [6]. [1] A pressure-sensitive adhesive composition containing an acrylic resin (A), the acrylic resin (A) is an acrylic resin obtained by copolymerizing a copolymerization component (a) including an acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms, an acrylate monomer (a2) having an alkyl group with 1 to 3 carbon atoms, and a 2-hydroxyethyl methacrylate monomer (a3); In the copolymerization component (a), The content of the acrylate monomer (a2) having an alkyl group having 1 to 3 carbon atoms is 20% by weight or more, A pressure-sensitive adhesive composition, characterized in that the content of 2-hydroxyethyl methacrylate monomer (a3) ​​is 6 wt % or more. [2] The pressure-sensitive adhesive composition according to [1], wherein the acrylic resin (A) has a glass transition temperature of more than -40°C. [3] The pressure-sensitive adhesive composition according to either [1] or [2], further comprising a crosslinking agent (B). [4] An adhesive for masking films, comprising the adhesive composition according to any one of [1] to [3]. [5] A masking adhesive film comprising an adhesive layer formed using the adhesive composition according to any one of [1] to [3]. Effect of the Invention

[0012] The pressure-sensitive adhesive composition of the present invention, when used as a pressure-sensitive adhesive, has excellent releasability and resistance to contamination of adherends, regardless of the peeling speed. Therefore, a pressure-sensitive adhesive obtained by using the pressure-sensitive adhesive composition can be suitably used as a pressure-sensitive adhesive film for masking, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below, but these are merely examples of preferred embodiments. In addition, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate. In addition, "acrylic resin" is a resin obtained by polymerizing a polymerization component containing at least one (meth)acrylate monomer. In addition, the "adhesive" in this invention is one that has tack at 25°C (room temperature) and adheres to an adherend with light pressure, such as that applied by hand, and the "film" conceptually encompasses sheets, films, and tapes.

[0014] The pressure-sensitive adhesive composition of the present invention contains an acrylic resin (A) copolymerized with a copolymerization component (a) including an acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms, an acrylate monomer (a2) having an alkyl group with 1 to 3 carbon atoms, and a 2-hydroxyethyl methacrylate monomer (a3), wherein the content of the acrylate monomer (a2) having an alkyl group with 1 to 3 carbon atoms in the copolymerization component (a) is 20% by weight or more, and the content of the 2-hydroxyethyl methacrylate monomer (a3) ​​is 6% by weight or more. The copolymerization components (a) of the acrylic resin (A) will be described below in order.

[0015] <Copolymer component (a) of acrylic resin (A)> [Acrylate Monomer (a1) Having an Alkyl Group Having 4 to 12 Carbon Atoms] Specific examples of the acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms include n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isodecyl acrylate, tridecyl acrylate, n-lauryl acrylate, etc. Among these, n-butyl acrylate and 2-ethylhexyl acrylate are preferred, and n-butyl acrylate is more preferred, in terms of excellent adhesive properties and excellent stability during polymerization. These acrylate monomers (a1) having an alkyl group with 4 to 12 carbon atoms can be used alone or in combination of two or more kinds.

[0016] The content of the acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms is preferably 10% by weight or more, more preferably 20 to 90% by weight, still more preferably 25 to 80% by weight, particularly preferably 30 to 70% by weight, and especially preferably 35 to 55% by weight, based on the copolymerization component (a) constituting the acrylic resin (A). If the content is too low, it becomes difficult to obtain the effects of the present invention, and the adhesive properties and durability tend to decrease.

[0017] [Acrylate Monomer (a2) Having an Alkyl Group Having 1 to 3 Carbon Atoms] Examples of the acrylate monomer (a2) having an alkyl group having 1 to 3 carbon atoms include methyl acrylate, ethyl acrylate, and propyl acrylate, and among these, methyl acrylate is preferred. These may be used alone or in combination of two or more.

[0018] From the viewpoint of adhesive properties, it is preferable that the copolymerization component (a) constituting the acrylic resin (A) does not contain a methacrylate monomer having an alkyl group having 1 to 3 carbon atoms.

[0019] The content of the acrylate monomer (a2) having an alkyl group having 1 to 3 carbon atoms is 20% by weight or more, preferably 25 to 80% by weight, more preferably 30 to 70% by weight, and further preferably 35 to 60% by weight, based on the copolymerization component (a) constituting the acrylic resin (A). If the content is too small, it becomes difficult to obtain the effects of the present invention, and the adhesive properties and durability tend to decrease.

[0020] The blending ratio [(a1) / (a2)] of the acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms and the acrylate monomer (a2) having an alkyl group with 1 to 3 carbon atoms is usually 85 / 15 to 20 / 80, preferably 80 / 20 to 30 / 70, more preferably 70 / 30 to 40 / 60 by weight in terms of high durability, adhesive properties and stain resistance of adherends. When the blending ratio is within this range, the effects of the present invention are easily obtained.

[0021] [2-Hydroxyethyl methacrylate monomer (a3)] The content of the 2-hydroxyethyl methacrylate monomer (a3) ​​is 6% by weight or more, more preferably 7 to 30% by weight, still more preferably 8 to 20% by weight, and particularly preferably 9 to 16% by weight, based on the copolymerization component (a) constituting the acrylic resin (A). If the content is too low, the adhesive properties and durability tend to decrease.

[0022] [Other monomers (a4)] The copolymerization component (a) constituting the acrylic resin (A) may contain a monomer (a4) other than the above (a1), (a2), and (a3) ​​within a range that does not impair the effects of the present invention (for example, within a range of 10% by weight or less of the copolymerization component (a)).

[0023] Examples of the other monomers (a4) include carboxy group-containing vinyl monomers such as (meth)acrylic acid, methacrylates having an alkyl group, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxypropylhexahydrophthalic acid, 2-(meth)acryloyloxyethylphthalic acid, 2-(meth)acryloyloxypropylphthalic acid, 2-(meth)acryloyloxyethylmaleic acid, 2-(meth)acryloyloxypropylmaleic acid, 2-(meth)acryloyloxyethylsuccinic acid, 2-(meth)acryloyloxypropylsuccinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate; Vinyl monomers containing an acid anhydride group, such as maleic anhydride and itaconic anhydride; Epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, glycidyl-α-ethyl acrylate, and 3,4-epoxybutyl (meth)acrylate; Amino group-containing (meth)acrylate vinyl monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; Vinyl monomers containing an amide group, such as (meth)acrylamide, Nt-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone acrylamide, maleic acid amide, and maleimide; Vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, (meth)acrylonitrile, vinyl chloride, vinyl acetate, and vinyl propionate; Examples of such monomers include divinylbenzene, ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, allyl (meth)acrylate, etc. Among these, from the viewpoints of heat resistance and stability during polymerization, carboxyl group-containing vinyl monomers are preferred, and acrylic acid is more preferred. The other monomers (a4) may be used alone or in combination of two or more kinds.

[0024] The content of the other monomer (a4) is preferably 10% by weight or less, more preferably 1% by weight or less, and even more preferably 0.3% by weight or less, based on the copolymerization component (a) constituting the acrylic resin (A). The lower limit is usually 0% by weight.

[0025] <Method for producing acrylic resin (A)> Next, a method for producing the acrylic resin (A) used in the present invention will be described. The acrylic resin (A) used in the present invention can be produced by, for example, mixing or dropping the copolymerization component (a) and a polymerization initiator into an organic solvent to polymerize using a copolymerization component (a) that is a combination of an acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms, an acrylate monomer (a2) having an alkyl group with 1 to 3 carbon atoms, a 2-hydroxyethyl methacrylate monomer (a3), and, if necessary, other monomers (a4).

[0026] The polymerization reaction can be carried out by a conventionally known polymerization method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc., and among these, solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is more preferred.

[0027] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0028] Among these organic solvents, ethyl acetate, acetone, methyl ethyl ketone, butyl acetate, toluene, and methyl isobutyl ketone are preferably used, and more preferably ethyl acetate, acetone, and methyl ethyl ketone, in view of the ease of polymerization reaction, the effect of chain transfer, the ease of drying during adhesive coating, and high safety. These organic solvents may be used alone or in combination of two or more kinds. The amount of these organic solvents used is usually 10 to 900 parts by weight per 100 parts by weight of the copolymerization component (a) constituting the acrylic resin (A).

[0029] Examples of polymerization initiators used in such solution radical polymerization include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(methylpropionic acid), which are normal radical polymerization initiators, and organic peroxides such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide, which can be appropriately selected and used according to the monomer to be used. These polymerization initiators may be used alone or in combination of two or more. The amount of these polymerization initiators used is usually 0.01 to 5% by weight based on the copolymerization component (a).

[0030] <Acrylic resin (A)> The weight average molecular weight of the acrylic resin (A) thus obtained is preferably 100,000 to 3,000,000, more preferably 200,000 to 1,500,000, even more preferably 300,000 to 1,000,000, and particularly preferably 400,000 to 800,000. If the weight average molecular weight is too small, durability tends to decrease, whereas if it is too large, a large amount of dilution solvent is required during production, drying properties decrease, and the amount of residual solvent in the pressure-sensitive adhesive layer increases, tending to decrease durability.

[0031] The dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 20 or less, more preferably 15 or less, and further preferably 10 or less. If the degree of dispersion is too high, reworkability and durability tend to decrease. The lower limit of the degree of dispersion is usually 1.

[0032] The weight-average molecular weight (Mw) is the weight-average molecular weight calculated based on the molecular weight of standard polystyrene. The high-performance liquid chromatograph (Waters Corporation, "Waters 2695 (main body)" and "Waters 2414 (detector)") was equipped with a Shodex GPC KF-806L column (molecular weight exclusion limit: 2 × 10 7 , Separation range: 100~2×10 7The measurement is performed by connecting three tubes in series: theoretical plate number: 10,000 plates / tube, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm. The number average molecular weight is also measured in the same way, and the dispersity (weight average molecular weight / number average molecular weight) is calculated from the number average molecular weight and weight average molecular weight.

[0033] The glass transition temperature (Tg) of the acrylic resin (A) is preferably above −40° C., more preferably −35 to 10° C., even more preferably −30 to 0° C., and particularly preferably −25 to −10° C., from the viewpoints of high-speed peelability and contamination resistance of the adherend. When the glass transition temperature is within this range, the effects of the present invention are easily obtained.

[0034] The glass transition temperature (Tg) is calculated by the following Fox formula.

number

[0035] That is, the glass transition temperature (Tg) of the acrylic resin (A) is a value calculated by applying the glass transition temperature and weight fraction of each monomer constituting the acrylic resin (A) as a homopolymer to the Fox equation. The glass transition temperature of the homopolymer of the monomers constituting the acrylic resin (A) is usually measured by a differential scanning calorimeter (DSC) and can be measured by a method in accordance with JIS K7121-1987 or JIS K 6240.

[0036] The viscosity of the acrylic resin (A) is adjusted with a solvent or the like, and the acrylic resin (A) solution is used in the pressure-sensitive adhesive composition of the present invention. The dilution concentration is preferably 10 to 60% by weight, more preferably 20 to 50% by weight in terms of resin content. From the viewpoint of ease of handling, the viscosity of the acrylic resin (A) solution is preferably 500 to 20,000 mPa·s, more preferably 1,000 to 18,000 mPa·s, and even more preferably 2,000 to 15,000 mPa·s. If the viscosity is too high, the fluidity decreases and handling tends to become difficult, whereas if the viscosity is too low, application of the resulting adhesive tends to become difficult.

[0037] The viscosity of the acrylic resin (A) solution is measured by subjecting the resin solution, whose temperature has been adjusted to 25° C., to a rotational viscometer method using a B-type viscometer.

[0038] <Crosslinking agent (B)> In order to improve adhesion to a substrate and to improve the durability of the pressure-sensitive adhesive composition of the present invention, it is preferable that the pressure-sensitive adhesive composition further contains a crosslinking agent (B) in addition to the acrylic resin (A).

[0039] The crosslinking agent (B) reacts with functional groups in the acrylic resin (A) to form a crosslinked structure, and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, metal chelate-based crosslinking agents, etc. Among these, it is preferable to use an isocyanate-based crosslinking agent in terms of improving adhesion to the substrate and excellent reactivity with the acrylic resin (A). The crosslinking agent (B) may be used alone or in combination of two or more kinds.

[0040] Examples of the isocyanate-based crosslinking agent include aromatic isocyanate-based crosslinking agents such as tolylene diisocyanate-based crosslinking agents such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, xylylene diisocyanate-based crosslinking agents such as 1,3-xylylene diisocyanate, diphenylmethane-4,4-diisocyanate and other diphenylmethane-based crosslinking agents, and naphthalene diisocyanate-based crosslinking agents such as 1,5-naphthalene diisocyanate; isophorone diisocyanate, 1,4-cyclohexane diisocyanate, and other diphenylmethane-based crosslinking agents. alicyclic isocyanate crosslinking agents such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and the like; and adducts, biuret forms, and isocyanurates of the above-mentioned isocyanate compounds.

[0041] Among these isocyanate-based crosslinking agents, tolylene diisocyanate-based crosslinking agents are preferred in terms of pot life and durability, xylylene diisocyanate-based crosslinking agents or isocyanurate skeleton-containing isocyanate-based crosslinking agents are preferred in terms of shortening the aging time, and aromatic ring-free isocyanate-based crosslinking agents are preferred in terms of yellowing resistance. Specifically, among these, tolylene diisocyanate, xylylene diisocyanate, an adduct of hexamethylene diisocyanate and trimethylolpropane, and a nurate are preferred in terms of excellent balance between durability, pot life, and crosslinking speed.

[0042] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, and diglycerol polyglycidyl ether.

[0043] Examples of the aziridine-based crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).

[0044] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, melamine resins, and the like.

[0045] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.

[0046] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.

[0047] Examples of the metal chelate crosslinking agent include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with acetylacetone or acetoacetyl ester.

[0048] When such a crosslinking agent (B) is used, its content is preferably 0.01 to 40 parts by weight, more preferably 1 to 40 parts by weight, even more preferably 3 to 30 parts by weight, and particularly preferably 5 to 20 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content is too low, durability tends to be easily reduced, while if the content is too high, stress relaxation tends to be reduced, making the substrate more susceptible to warping or requiring long-term aging. The equivalent of the crosslinking agent (B) relative to the acrylic resin (A) is preferably 0.1 to 2, more preferably 0.3 to 1.5, particularly preferably 0.5 to 1.3, and further preferably 0.7 to 1.1, from the viewpoint of adhesive properties.

[0049] <Other ingredients> The pressure-sensitive adhesive composition of the present invention may contain other known additives, such as polyether compounds of polyalkylene glycols such as polypropylene glycol, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, foils, etc., which can be added appropriately depending on the application. In addition, a redox system in which a reducing agent is added may be adopted within a controllable range. These can be used alone or in combination of two or more. The amount of these additives is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 1 part by weight or less, based on 100 parts by weight of the acrylic resin (A). The lower limit is usually 0 part by weight.

[0050] Thus, the pressure-sensitive adhesive composition of the present invention can be obtained by mixing the acrylic resin (A), preferably further the crosslinking agent (B), and further other optional components as required.

[0051] In order to effectively exert the effects of the present invention, the proportion of the acrylic resin (A) in the entire pressure-sensitive adhesive composition is preferably 50 to 99.9% by weight, more preferably 60 to 99% by weight, even more preferably 70 to 95% by weight, and particularly preferably 80 to 90% by weight.

[0052] The mixing method is not particularly limited, and various methods can be used, such as a method of mixing the components all at once, or a method of mixing any components and then mixing the remaining components all at once or sequentially.

[0053] <Adhesive> The adhesive obtained from the adhesive composition of the present invention has excellent peeling property and anti-contamination property of adherend regardless of peeling speed.Therefore, this adhesive can be applied to various substrates to be made into adhesive film, and can be suitably used as adhesive for various members such as surface protection film, display label, masking tape, adhesive for touch panel, adhesive for sensor such as ITO, adhesive for vehicle, optical film, polarizing plate, etc., and is particularly suitable for use as adhesive for masking film, particularly as adhesive for masking film for optical film.

[0054] <Adhesive layer> The pressure-sensitive adhesive composition can be used to make a pressure-sensitive adhesive, and such a pressure-sensitive adhesive can be used to form a pressure-sensitive adhesive layer such as a pressure-sensitive adhesive film. When using a crosslinking agent (B) to form such a pressure-sensitive adhesive layer, it is preferable to adjust the total amount of the crosslinking agent (B) added and to fully consider the effects of the crosslinking temperature and time.

[0055] The crosslinking temperature and time can be adjusted depending on the crosslinking agent (B) used. The crosslinking temperature is preferably 170° C. or less.

[0056] <Adhesive film> The adhesive film of the present invention can be obtained by crosslinking the above-mentioned adhesive composition to form an adhesive, and then laminating an adhesive layer made of such an adhesive onto a base film such as a plastic film. It is preferable that the pressure-sensitive adhesive film further includes a release film on the surface of the pressure-sensitive adhesive layer opposite to the base film.

[0057] Examples of methods for producing the above-mentioned adhesive film include (1) a method in which an adhesive composition is applied onto a base film, dried, a release film is laminated, and an aging treatment is performed at least at room temperature or at elevated temperature, and (2) a method in which an adhesive composition is applied onto a release film, dried, a base film is laminated, and an aging treatment is performed at least at room temperature or at elevated temperature.

[0058] Such aging treatment is carried out to balance the adhesive properties as the reaction time of the chemical crosslinking of the adhesive, and the aging conditions are usually a temperature of 20 to 70°C and a time of 1 to 30 days, and specifically, for example, 23°C for 1 to 20 days or 40°C for 1 to 7 days.

[0059] When applying the pressure-sensitive adhesive composition, it is preferable to dilute the pressure-sensitive adhesive composition with a solvent before application. The dilution concentration is preferably such that the heating residue (resin content concentration) is 5 to 60% by weight, and particularly preferably 20 to 50% by weight.

[0060] The solvent is not particularly limited as long as it dissolves the pressure-sensitive adhesive composition, and examples of the solvent that can be used include ester solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate and methyl ethyl ketone are preferably used in terms of solubility, drying property, cost, etc. These may be used alone or in combination of two or more kinds.

[0061] The pressure-sensitive adhesive composition can be applied by a conventional method such as roll coating, die coating, gravure coating, comma coating, or screen printing.

[0062] The thickness of the adhesive layer in the obtained adhesive film is preferably 1 to 100 μm, more preferably 5 to 30 μm, and even more preferably 8 to 20 μm. If the adhesive layer is too thin, the thickness precision and adhesive strength tend to decrease, whereas if it is too thick, the adhesive film tends to protrude from the edge when rolled.

[0063] The gel fraction of the pressure-sensitive adhesive layer produced by the above method is preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more, from the viewpoints of adhesion to the substrate, reworkability, and holding power. If the gel fraction is too low, the cohesive strength is reduced, and adhesive residue tends to be left during rework, and holding power tends to be reduced.

[0064] The gel fraction is a measure of the degree of crosslinking (degree of curing) and is calculated, for example, by the following method: An adhesive is picked from an adhesive film having an adhesive layer formed on a substrate, the adhesive is wrapped in a 200-mesh SUS wire netting and immersed in ethyl acetate at 23°C for 24 hours, and the weight percentage of the insoluble adhesive remaining in the wire netting relative to the weight of the adhesive before immersion in ethyl acetate is defined as the gel fraction.

[0065] The above adhesive film is aged at 40°C for 7 days, and then a 25 mm x 100 mm test piece is prepared and applied to a stainless steel plate (SUS304BA plate) with pressure using a 2 kg rubber roller in two passes in an atmosphere of 23°C and relative humidity of 50%. After leaving to stand in the same atmosphere for 30 minutes, the film is peeled off at a peel angle of 180° and a peel speed of 0.3 m / min. The adhesive strength when peeled off is preferably 0.1 N / 25 mm or more and 1.0 N / 25 mm or less, from the viewpoint of preventing adhesive residue and the occurrence of adhesive marks on the surface of the adherend, and more preferably 0.2 N / 25 mm or more and less than 0.5 N / 25 mm.

[0066] In addition, the above-mentioned adhesive film is aged at 40°C for 7 days, and then a test piece of 25mm x 100mm is prepared, and the test piece is pressed and attached to a stainless steel plate (SUS304BA plate) with a 2kg rubber roller in two round trips at 23°C and a relative humidity of 50%, and the adhesive strength when peeled off at a peel angle of 180° and a peel speed of 10m / min is preferably 0.1N / 25mm or more and 1.0N / 25mm or less from the viewpoint of preventing adhesive residue and adhesive marks on the adherend surface, and more preferably 0.2N / 25mm or more and less than 0.5N / 25mm. Within this range, adhesive residue and adhesive marks on the adherend surface tend to be prevented.

[0067] The pressure-sensitive adhesive film of the present invention is used by laminating the pressure-sensitive adhesive layer surface to the surface of an adherend, either directly or, in the case of a film having a release film, after removing the release film.

[0068] The adhesive film of the present invention is made using an adhesive composition that has excellent peeling properties and resistance to contamination of the adherend, regardless of the peeling speed, and therefore can be suitably used as an adhesive film for various components such as surface protection films, display labels, masking tapes, adhesive films for touch panels, adhesive films for sensors such as ITO, adhesive films for vehicles, optical films, polarizing plates, etc., and is particularly suitably used as an adhesive film for masking, and particularly as an adhesive film for optical films. EXAMPLES

[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.

[0070] First, the following materials were prepared prior to the experiment.

[0071] <Acrylic resin> Acrylic resin (A) or (A') was produced according to the following production method. The composition and physical properties of each acrylic resin are shown in Table 1 below. The weight average molecular weight (Mw), dispersity, and glass transition temperature (Tg) of acrylic resin (A) or (A') were measured according to the above-mentioned methods. The viscosity was measured according to the viscometer method using a Brookfield B type rotational viscometer as specified in JIS K7117-1 (1999).

[0072] [Production Example 1: Production of acrylic resin (A-1)] In a reactor equipped with a thermometer, a stirrer, a dropping funnel and a reflux condenser, 83.3 parts of ethyl acetate and 16.7 parts of methyl ethyl ketone were charged, and the internal temperature was raised to the boiling point while stirring, and then a mixed solution of 39.85 parts of n-butyl acrylate (BA) (a1), 50 parts of methyl acrylate (a2), 10 parts of 2-hydroxyethyl methacrylate (a3), and 0.15 parts of acrylic acid (a4) was dropped over 2 hours. Next, during the polymerization, 7.5 parts of ethyl acetate and 0.023 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were added and reacted, and then 12.5 parts of ethyl acetate and 0.05 parts of AIBN were added successively, and the reaction was continued under reflux for 7.0 hours, followed by dilution with 13 parts of methyl ethyl ketone to obtain a solution of acrylic resin (A-1).

[0073] [Production of Acrylic Resins (A-2), (A-3) and (A'-1) to (A'-3)] An acrylic resin solution was obtained using the monomer composition shown in Table 1 below in the same manner as in the case of the acrylic resin (A-1).

[0074] [Table 1]

[0075] <Isocyanate-based crosslinking agent (B)> Isocyanate-based crosslinking agent (B-1): Coronate HX (manufactured by Tosoh Corporation)

[0076] <Example 1> [Preparation of Pressure-Sensitive Adhesive Composition] The above obtained acrylic resin (A-1) solution (100 parts in terms of resin content) was mixed with 13.9 parts (0.9 equivalents) of an isocyanate-based crosslinking agent (B-1) to prepare a pressure-sensitive adhesive composition.

[0077] [Preparation of adhesive film] The adhesive composition prepared above was applied to a PET film (thickness 38 μm) substrate so that the adhesive layer would have a thickness of 10 μm after drying, and then dried for 2 minutes at 100° C. Thereafter, a release-treated PET film (release film: thickness 38 μm) was attached to the coated surface to protect the adhesive layer, and an adhesive film was produced. The resulting pressure-sensitive adhesive film was subjected to the following evaluations, and the results are shown in Table 2 below.

[0078] <Removability> [Peeling speed: 0.3 m / min] The adhesive film obtained above was aged at 40°C for 7 days, and then a 25mm x 100mm test piece was prepared. The release film was removed and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. The piece was then left to stand for 30 minutes in the same atmosphere, after which the 180° peel strength (N / 25mm) was measured at a peel speed of 0.3m / min and evaluated according to the following criteria. (Evaluation Criteria) ○ 0.2N / 25mm or more, less than 0.5N / 25mm △ 0.1N / 25mm or more, less than 0.2N / 25mm Or 0.5N / 25mm or more, less than 1.0N / 25mm × Less than 0.1N / 25mm or 1.0N / 25mm or more

[0079] (Peeling speed: 10m / min) The adhesive film obtained above was aged at 40°C for 7 days, and then a 25mm x 100mm test piece was prepared. The release film was removed and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. The piece was then left to stand for 30 minutes in the same atmosphere, after which the 180° peel strength (N / 25mm) was measured at a peel speed of 10m / min and evaluated according to the following criteria. (Evaluation Criteria) ○ 0.2N / 25mm or more, less than 0.5N / 25mm △ 0.1N / 25mm or more, less than 0.2N / 25mm Or 0.5N / 25mm or more, less than 1.0N / 25mm × Less than 0.1N / 25mm or 1.0N / 25mm or more

[0080] <Stain resistance of adherend> [Peeling speed: 0.3 m / min] The adhesive film obtained above was aged at 40°C for 7 days, and then a 25mm x 100mm test piece was prepared. The release film was removed and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. The piece was then left to stand in the same atmosphere for 30 minutes, after which the condition of the adherend surface after 180° peeling at a peeling speed of 0.3m / min was observed and evaluated according to the following criteria. (Evaluation Criteria) ○: No adhesive residue or adhesive marks were found △: No adhesive residue was found, but some adhesive marks were found. ×: Adhesive residue was observed

[0081] (Peeling speed: 10m / min) The adhesive film obtained above was aged at 40°C for 7 days, and then a 25mm x 100mm test piece was prepared. The release film was removed and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. The piece was then left to stand in the same atmosphere for 30 minutes, after which the condition of the adherend surface after 180° peeling at a peeling speed of 10m / min was observed and evaluated according to the following criteria. (Evaluation Criteria) ○: No adhesive residue or adhesive marks were found △: No adhesive residue was found, but some adhesive marks were found. ×: Adhesive residue was observed

[0082] <Examples 2 to 3, Comparative Examples 1 to 3> Pressure-sensitive adhesive compositions were prepared and pressure-sensitive adhesive films were produced in the same manner as in Example 1, except that the acrylic resins shown in Table 2 were used. Using the obtained pressure-sensitive adhesive compositions and pressure-sensitive adhesive films, evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2 below.

[0083] [Table 2]

[0084] From Table 2 above, in the Examples, the adhesive strength was excellent regardless of the peeling speed, whereas in Comparative Example 1, which used an acrylic resin obtained from a copolymerization component with less 2-hydroxyethyl methacrylate, component (a3), which serves as a crosslinking point, the adhesive strength was poor, and in Comparative Example 2, which used an acrylic resin obtained from a copolymerization component with less methyl acrylate, component (a2), the adhesive strength was excellent at low peeling speed but poor at high peeling speed. Also, in Comparative Example 3, which used an acrylic resin obtained from a copolymerization component using methyl methacrylate instead of methyl acrylate, the adhesive strength was very low regardless of the peeling speed, and was poor. This shows that it is important that the acrylic resin (A) in the pressure-sensitive adhesive composition contains at least certain amounts of methyl acrylate and 2-hydroxyethyl methacrylate.

[0085] Furthermore, when used as an adhesive, the adhesive compositions of the examples have excellent peeling properties and resistance to contamination of the adherend, regardless of the peeling speed, and are therefore suitable for use as adhesives for masking films and masking adhesive films. [Industrial Applicability]

[0086] The adhesive obtained from the adhesive composition of the present invention has excellent peeling property and anti-contamination property of adherend regardless of peeling speed.Therefore, this adhesive can be applied to various substrates to be made into adhesive film, and can be suitably used as adhesive for various members such as surface protection film, display label, masking tape, adhesive for touch panel, adhesive for sensor such as ITO, adhesive for vehicle, optical film, polarizing plate, etc., and is particularly suitable for use as adhesive for masking film, particularly as adhesive for masking film for optical film.

Claims

1. A pressure-sensitive adhesive composition comprising an acrylic resin (A) and a crosslinking agent (B), the acrylic resin (A) is an acrylic resin obtained by copolymerizing a copolymerization component (a) including an acrylate monomer (a1) having an alkyl group with 4 to 12 carbon atoms, an acrylate monomer (a2) having an alkyl group with 1 to 3 carbon atoms, and a 2-hydroxyethyl methacrylate monomer (a3); In the copolymerization component (a), The content of the acrylate monomer (a2) having an alkyl group having 1 to 3 carbon atoms is 20% by weight or more, The content of 2-hydroxyethyl methacrylate monomer (a3) ​​is 6% by weight or more, a mixing ratio [(a1) / (a2)] of the acrylate monomer (a1) having an alkyl group having 4 to 12 carbon atoms to the acrylate monomer (a2) having an alkyl group having 1 to 3 carbon atoms is 70 / 30 to 40 / 60 by weight, A pressure-sensitive adhesive composition, characterized in that the content of the crosslinking agent (B) is 5 to 40 parts by weight per 100 parts by weight of the acrylic resin (A).

2. The pressure-sensitive adhesive composition according to claim 1, wherein the acrylic resin (A) has a glass transition temperature of more than -40°C.

3. A pressure-sensitive adhesive for masking films, comprising the pressure-sensitive adhesive composition according to claim 1 or 2.

4. A masking adhesive film, comprising an adhesive layer formed using the adhesive composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Adhesive composition for re-peelable surface-protecting sheet and re-preelable surface-protecting sheet

    JP2004067958A

  • Pressure-sensitive adhesive composition for optical member surface protective film and optical member surface protective film

    JP2005097451A

  • Acrylic adhesive for surface protective film

    JP2011231203A

  • Peelable pressure-sensitive adhesive composition, peelable pressure-sensitive adhesive layer, and peelable pressure-sensitive adhesive sheet

    JP2013079360A

  • Adhesive composition, adhesive agent by crosslinking the same, adhesive agent for masking film, adhesive agent for heat resistant adhesive film and heat resistant adhesive film for masking

    JP2017115078A